1980
DOI: 10.1038/icb.1980.26
|View full text |Cite
|
Sign up to set email alerts
|

PHYSICOCHEMICAL AND IMMUNOCHEMICAL CHARACTERIZATION OF THE ALLERGENS FROM THE MITE DERMATOPHAGOIDES PTERONYSSINUS

Abstract: Summary The physicochemical and immunochemical characteristics of the allergens from Dermatophagoides pteroyssinus have been described, in particular those for the allergens designated Dpt 4 and Dpt 12. Dpt 4 is a high molecular weight allergen with an apparent molecular weight of 274,000 daltons and a pI of 4.5. In contrast, the antigenically unrelated Dpt 12 has an apparent molecular weight of 24,000 daltons and a pI 6.6. Both allergens demonstrate heterogeneity, either in molecular weight or pI. Dpt 12 appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

1983
1983
1991
1991

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 0 publications
2
24
0
Order By: Relevance
“…The Group I allergens (Derp I, Derf I, Der m I) are heat-labile glycoproteins (relative molecular mass, Mr, 25 000), which are heterogeneous on isoelectricfocusing (IEF) (pI, 4.7-7.4) and are excreted in faeces (5,9,10,27,(31)(32)(33). These allergens appear to be structural homologues and have very similar Nterminal amino acid sequences.…”
Section: Identification and Standardizationmentioning
confidence: 99%
“…The Group I allergens (Derp I, Derf I, Der m I) are heat-labile glycoproteins (relative molecular mass, Mr, 25 000), which are heterogeneous on isoelectricfocusing (IEF) (pI, 4.7-7.4) and are excreted in faeces (5,9,10,27,(31)(32)(33). These allergens appear to be structural homologues and have very similar Nterminal amino acid sequences.…”
Section: Identification and Standardizationmentioning
confidence: 99%
“…Ste ward as a lyophilised extract from house dust mite [16]. L. perenne (rye-grass pollen), purchased from Greer Laboratories, USA, was defatted in dry ether, extracted with 0.1 M NH.,HCO,.…”
Section: Methodsmentioning
confidence: 99%
“…Studies from this laboratory have shown that ex tracts of the house dust mite, Dermatophagoides pter onyssinus, contain an allergen designated Dpt 4 [19,20] which exhibits certain physicochemical character istics differing markedly from those associated with previously described allergens from other sources. For example, by gradient polyacrylamide gel electro phoresis the bulk of the allergen was found to have an apparent molecular weight of 274,000 daltons, a value outside the commonly accepted molecular weight range of 10,000-60,000 daltons circumscribing the al lergens from grass pollens and danders [13].…”
Section: Introductionmentioning
confidence: 99%
“…For example, by gradient polyacrylamide gel electro phoresis the bulk of the allergen was found to have an apparent molecular weight of 274,000 daltons, a value outside the commonly accepted molecular weight range of 10,000-60,000 daltons circumscribing the al lergens from grass pollens and danders [13]. In addi tion, Dpt 4 demonstrated heterogeneity with regard to both molecular weight and binding to the lectin Con-A [19,20], Further, this allergen was shown to contain the hapten phosphorylcholine (PC) as judged by its reactivity with the PC-specific murine IgA mye loma S107 [20,21].…”
Section: Introductionmentioning
confidence: 99%